AN ERROR ANALYSIS OF ARGUMENTATIVE ESSAY (CASE STUDY AT UNIVERSITY MUHAMMADIYAH OF METRO) - Fenny - Thresia (Premise: Journal of English Education and Applied Linguistics, 2013)
The purpose of this study was study analyze the students’ error in writing argumentative essay. The researcher focuses on errors of verb, concord and learner language. This study took 20 students as the subject of research from the third semester. The data took from observation and documentation. Based on the result of the data analysis there are some errors still found on the student’s argumentative essay in English writing? The common errors which repeatedly appear are verb. The second is concord, and learner languages are the smallest error. From 20 samples that took, the frequency the errors of verb are 12 items (60%), concord are 8 items (40%), learner languages are 7 items (35%). As a result, verb has the biggest number of common errors.